The effect of slow-stroke back massage on fatigue and sleep quality in hemodialysis patients: A clinical trial study - Zeinab Raiesifar; Shahram Molavynejad; Afsaneh Raiesifar; Elham Maraghi; Mojtaba Vaismoradi; Aliraeza Helalat (حیات, 2021)
Background & Aim: Fatigue and sleep disorders are the most common physical complaints in hemodialysis patients. It seems necessary to find effective, low-complication and cost-effective treatments to alleviate these problems. The aim of this study was to examine the effect of slow-stroke back massage on the level of fatigue and sleep quality in hemodialysis patients. Methods & Materials: In this randomized controlled trial, 82 hemodialysis patients hospitalized in Shahid Beheshti hospital in Abadan in 2018, were selected based on the inclusion criteria and were allocated to either the intervention or control group using permuted block randomization (4 blocks). The intervention group underwent massage therapy for 12 sessions. The numerical rating scale for measuring fatigue and the Pittsburgh Sleep Quality Questionnaire were completed 14 times and three times respectively, by both groups. Data were analyzed through the SPSS software version 22 using descriptive statistical tests, independent t-test and repeated measures analysis of variance. Results: The results showed that before the intervention, there was no statistically significant difference in demographic variables between the intervention and control groups (P>0.05). Significance of group and time interactions for fatigue score showed that the trend of changes in mean fatigue scores was different in the two groups and over the study time period (P<0.001). Also, there was a statistically significant difference between the two groups in the total score of sleep quality and all sleep components except two components (mental quality of sleep and sleep disorders) (P<0.05). Conclusion: This study showed that slow-stroke back massage improves fatigue and sleep quality in hemodialysis patients. Therefore, it is recommended as an inexpensive, effective and uncomplicated method in hemodialysis patients. Clinical trial registry: IRCT20181119041702N1